The tobacco GNTI stem region harbors a strong motif for homomeric protein complex formation - Schoberer, Jennifer; Izadi, Shiva; Kierein, Carolina; Vavra, Ulrike; König-Beihammer, Julia; Ruocco, Valentina; Grünwald-Gruber, Clemens; Castilho, Alexandra; Strasser, Richard (Frontiers in Plant Science, 2023)
Introduction The Golgi apparatus of plants is the central cellular organelle for glycan processing and polysaccharide biosynthesis. These essential processes are catalyzed by a large number of Golgi-resident glycosyltransferases and glycosidases whose organization within the Golgi is still poorly understood. Methods Here, we examined the role of the stem region of the cis/medial Golgi enzyme N-acetylglucosaminyltransferase I (GNTI) in homomeric complex formation in the Golgi of Nicotiana benthamiana using biochemical approaches and confocal microscopy. Results Transient expression of the N-terminal cytoplasmic, transmembrane, and stem (CTS) regions of GNTI leads to a block in N-glycan processing on a co-expressed recombinant glycoprotein. Overexpression of the CTS region from Golgi α-mannosidase I, which can form in planta complexes with GNTI, results in a similar block in N-glycan processing, while GNTI with altered subcellular localization or N-glycan processing enzymes located further downstream in the Golgi did not affect complex N-glycan processing. The GNTI-CTS-dependent alteration in N-glycan processing is caused by a specific nine-amino acid sequence motif in the stem that is required for efficient GNTI-GNTI interaction. Discussion Taken together, we have identified a conserved motif in the stem region of the key N-glycan processing enzyme GNTI. We propose that the identified sequence motif in the GNTI stem region acts as a dominant negative motif that can be used in transient glycoengineering approaches to produce recombinant glycoproteins with predominantly mannosidic N-glycans.